Superstructure Strategy: Do Indonesian EFL Learners Use It? - Evy C Ridwan (TEFLIN Journal: A publication on the teaching and learning of English, 1997)
Abstract: This paper reports on a study conducted among Indonesian undergraduate students majoring in English as a Foreign Language (EFL). One strategy that learners generally use to understand the main ideas of an expository text is the superstructure strategy (i.e., utilizing the text structure to understand the main ideas). While research in English as First Language reading has demonstrated the benefit of using this strategy, little do we know whether Indonesian EFL learners use this strategy in reading and whether this strategy is beneficial to them or not. Two versions of an expository text were developed: One version had an explicit text structure, with the inclusion of discourse markers, to elicit learners to use the superstructure strategy; the other was without discourse markers. It was hypothesized that learners who read the version with an explicit text structure would utilize the superstructure strategy thereby comprehending main ideas better than those who read the other version. Additionally, to confirm the hypothesis learners were also asked to answer a questionnaire developed from OMalley and Chamot (1993) followed by an interview to find out if EFL learners used other strategies to comprehend main ideas.